IMPLEMENTASI PEMENUHAN HAK PENYANDANG CACAT DALAM MEMPEROLEH PEKERJAAN PADA PERUSAHAAN NEGARA DAN SWASTA DI KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 4 TAHUN 1997 TENTANG PENYANDANG CACAT - Rizano '; Firdaus '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The Republic of Indonesia is known as the state that carries the idea of a welfare state (welfare state) this is because in the preamble to the Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 are one of the country's goal is to express the idea of the welfare state. The aim is to achieve a welfare state and welfare society prosperity where in this country and the means of its equipment or apparatus to serve the interests and welfare prosperity community, including providing social security, such as health service, poor maintenance and security neglected children. There are several legal instruments that are born to protect the rights of disabled people to work, they carry are listed in the Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, Undang-Undang Nomor 4 Tahun 1997 Tentang Penyandang Cacat, Undang-Undang Nomor 19 Tahun 2011 Tentang Pengesahaan Konvensi Mengenai Hak-Hak Penyandang Disabilitas, Undang-Undang Nomor 39 Tahun 1999 Tentang Hak Asasi Manusia Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan, Undang Dasar Negara Republik Indonesia Tahun 1945 dan Peraturan Pemerintah Republik Indonesia Nomor 43 Tahun 1998 Tentang Upaya Peningkatan Kesejateraan Sosial Penyandang Cacat.The purpose of this study is to investigate the implementation of the fulfillment of the rights of people with disabilities to obtain employment in the state and private companies in the city of Pekanbaru as well as the constraints and what efforts the fulfillment implementation rights of disabled people in obtaining employment in the city of Pekanbaru.This study is a descriptive sociological research, which consists of primary data, secondary and tertiary. Data collection tools such as interviews and literature study. The data have been collected and will be analyzed qualitatively grouped and diseimpulkan deductively.Implementation of the fulfillment of rights of persons with disabilities in obtaining employment in the state and private companies in the city of Pekanbaru is currently not running at max, because there are many companies that exist in the city of Pekanbaru kewajibanmya not implement quotas to people with disabilities with 1: 100, even though the law has been set clear penalties for companies who violate. Although there are still many companies that employ more than 100 people turned out to not hire a single person with a disability. But the fact is there are many people with disabilities who have not guaranteed the fulfillment of their right to work. Keywords: Human Rights, People with Disabilities, Employment